The Role of Registered Dietitians in Cancer Palliative Care: Responsibilities, Challenges, and Interdisciplinary Collaboration—A Cross-Sectional Survey - Saori Koshimoto; Koji Amano; Naoharu Mori; Atsuko Imai; Manami Sasaki; Miho Miyajima; Takashi Takeuchi (Current Oncology)
Registered dietitians (RDs) in palliative care help maintain patients’ quality of life by providing personalized nutritional support that alleviates eating-related distress. This study aimed to clarify the role of RDs in palliative care by examining their responsibilities and challenges in caring for cancer patients. A nationwide mailed survey was conducted in 2022, focusing on RDs involved in cancer palliative care. One RD per facility was included from all 501 hospitals accredited by Japan’s Ministry of Health, Labour and Welfare. Multivariate analysis identified factors related to collaboration with palliative care teams and challenges in cancer care. Responses from 325 RDs (63.9%) across 325 hospitals (63.9%) were analyzed. Among RDs who consistently collaborated with the palliative care team (PCT), significant associations (p < 0.05) were found with exclusive engagement in cancer/palliative care, providing nutritional counseling to inpatients, the frequency of ward rounds, and individualized meal provision. Challenges included the following: “I struggled with determining appropriate food choices for patients unable to eat”, and “Metabolic complications like cachexia hindered my ability to provide adequate support”. RDs play a crucial role in providing individualized meals for cancer patients through PCT collaboration and ward rounds. To ensure effective support in challenging situations, RDs must be exclusively engaged in palliative care and receive specialized education.